Indonesian Government Bureaucracy In The Perspective Of Reinventing Government: “How The Entrepreneurial Spirit Is Transforming The Public Sector” - Haeruddin; Toding, Sukanto; Nashar , Abdul (Arden Jaya Publisher, 2025)
The mandate of the Government of the Republic of Indonesia is to be more independent and improve its performance in managing its potential, as well as increasing public participation in the implementation of regional government policies, both at the provincial and district/city levels in Indonesia. The concept of